Selective Sugar Recognition by Anthracene-Type Boronic Acid Fluorophore/Cyclodextrin Supramolecular Complex Under Physiological pH Condition - Sugita, Ko; Tsuchido, Yuji; Kasahara, Chisato; Casulli, Maria Antonietta; Fujiwara, Shoji; Hashimoto, Takeshi; Hayashita, Takashi (Frontiers in Chemistry, 2019)
We synthesized novel PET (photoinduced electron transfer) type fluorescence glucose probe 1 ((4-(anthracen-2-yl-carbamoyl)-3-fluorophenyl)boronic acid), which has a phenylboronic acid (PBA) moiety as the recognition site and anthracene as the fluorescent part. Although the PBA derivatives dissociate and bind with sugar in the basic condition, our new fluorescent probe can recognize sugars in the physiological pH by introducing an electron-withdrawing fluorine group into the PBA moiety. As a result, the pKa value of this fluorescent probe was lowered and the probe was able to recognize sugars at the physiological pH of 7.4. The sensor was found to produce two types of fluorescent signals, monomer fluorescence and dimer fluorescence, by forming a supramolecular 2:1 complex of 1 with glucose inside a gamma-cyclodextrin (gamma-CyD) cavity. Selective ratiometric sensing of glucose by the 1/gamma-CyD complex was achieved in water at physiological pH.